2022
DOI: 10.3390/cancers15010173
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors and Pregnancy: Analysis of the VigiBase® Spontaneous Reporting System

Abstract: In pregnancy, immune checkpoint pathways are involved in the maintenance of fetomaternal immune tolerance. Preclinical studies have shown that immune checkpoint inhibitors (ICIs) increase the risk of fetal death. Despite the fact that using ICIs in pregnant women and women of childbearing potential is not recommended, some case reports of ICI exposure in pregnancy have been published showing favorable fetal outcomes. This study aimed to gain further insight into ICI safety in pregnancy by querying VigiBase®, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…None of the 45 explored maternofetal outcomes were overreported in the ICI-exposed group compared with the group exposed to other anticancer drugs. These findings align with a recent pharmacovigilance study using VigiBase that revealed no discernible patterns of maternal, fetal, or newborn toxic effects and no signals of disproportionate reporting within the ICI group compared with the other anticancer agents group . However, that study had several limitations.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…None of the 45 explored maternofetal outcomes were overreported in the ICI-exposed group compared with the group exposed to other anticancer drugs. These findings align with a recent pharmacovigilance study using VigiBase that revealed no discernible patterns of maternal, fetal, or newborn toxic effects and no signals of disproportionate reporting within the ICI group compared with the other anticancer agents group . However, that study had several limitations.…”
Section: Discussionsupporting
confidence: 83%
“…In oncology, existing guidelines stipulate that medical professionals should closely observe and report any instances of pregnancy during both clinical trials and regular treatment. Recently, a study analyzed VigiBase reports involving ICI exposure during the peripregnancy period and potential associations with pregnancy-related outcomes . The analysis was restricted to spontaneous abortion, fetal growth restriction, and premature birth.…”
Section: Introductionmentioning
confidence: 99%
“…VigiBase is the World Health Organization's (WHO) global pharmacovigilance database of safety reports of suspected SARs that was developed and maintained by the WHO-Uppsala Monitoring Centre (WHO-UMC). It collects report forms of suspected SARs from more than 170 national pharmacovigilance centres participating in the WHO Programme for International Drug Monitoring (WHO PIDM) (Noseda et al, 2022).…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…VigiBase was also previously investigated to address the fetal toxic effects of immune checkpoint inhibitors, for which no significant toxic effect was found. 10 The objective of this study was to perform a large-scale descriptive analysis of pregnancy and fetal or newborn outcomes after exposure to anti-ERBB2 agents and to determine the reporting odds ratio (ROR) of adverse pregnancy and fetal outcomes after exposure to anti-ERBB2 drugs relative to other non-anti-ERBB2 anticancer drugs in a case-control disproportionality analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, current guidelines recommend that (1) any pregnancy occurring during a trial or routine oncologic care should be monitored and that both (2) maternofetal adverse drug reactions and (3) outcomes of maternofetal exposure to contraindicated drugs, such as anticancer drugs, should be reported to pharmacovigilance institutions, including normal pregnancies, and ultimately reported to VigiBase. VigiBase was also previously investigated to address the fetal toxic effects of immune checkpoint inhibitors, for which no significant toxic effect was found …”
Section: Introductionmentioning
confidence: 99%